Media sebagai Penyampai Pesan atau Pembentuk Realitas? Kajian Filsafat Komunikasi: Media as Message Conveyer or Reality Shaper? A Study in Philosophy of Communication - Davina Nurul Ramadhani (Universitas Bengkulu, 2026)
This article examines the role of media as a conveyor of messages or a shaper of social reality from the perspective of the philosophy of communication science. This study uses a philosophical approach that encompasses ontology, epistemology, and axiology to explore how the media shapes meaning, knowledge, and values in society. Using a qualitative literature review method, this study analyzes academic publications over the past five years related to the media and the formation of reality. The findings show that the media not only conveys information, but also actively frames, filters, and reconstructs social reality through practices of representation, narrative selection, and digital mediation. The media therefore plays an important role in shaping what is known and how reality is perceived. Understanding the media as a shaper of reality highlights the importance of ethical responsibility in contemporary communication practices. Keyword: Media, social reality, philosophy of communication, reality constuction